2019
DOI: 10.1186/s12933-019-0845-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of pemafibrate administration in patients with dyslipidemia: a systematic review and meta-analysis

Abstract: BackgroundUsing a meta-analysis of randomized controlled trials (RCTs), this study aimed to investigate the efficacy and safety of pemafibrate, a novel selective peroxisome proliferator-activated receptor α modulator, in patients with dyslipidemia.MethodsA search was performed using the MEDLINE, Cochrane Controlled Trials Registry, and ClinicalTrials.gov databases. We decided to employ RCTs to evaluate the effects of pemafibrate on lipid and glucose metabolism-related parameters in patients with dyslipidemia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 39 publications
(45 reference statements)
1
47
0
Order By: Relevance
“…Other studies suggest that fibrates may also have beneficial effects on microvascular outcomes, including During the trial period, fibrate add-on therapy reduced triglycerides and VLDL-C beyond that achieved with statins only, but HDL-C was increased by only a limited amount. These findings have been observed in other clinical trials of fibrate-for example in the Fenofibrate Intervention and Event Lowering in Diabetes (FIELD) study, allocation to fenofibrate resulted in a 20% reduction of baseline TG, but HDL-C remained almost unchanged at study close [30][31][32]. The improvement of the triglyceriderich environment may explain the reduced risk of CVD observed during the trial period in these patients [15,33].…”
Section: Discussionsupporting
confidence: 64%
“…Other studies suggest that fibrates may also have beneficial effects on microvascular outcomes, including During the trial period, fibrate add-on therapy reduced triglycerides and VLDL-C beyond that achieved with statins only, but HDL-C was increased by only a limited amount. These findings have been observed in other clinical trials of fibrate-for example in the Fenofibrate Intervention and Event Lowering in Diabetes (FIELD) study, allocation to fenofibrate resulted in a 20% reduction of baseline TG, but HDL-C remained almost unchanged at study close [30][31][32]. The improvement of the triglyceriderich environment may explain the reduced risk of CVD observed during the trial period in these patients [15,33].…”
Section: Discussionsupporting
confidence: 64%
“…This study also showed that pema brate decreased TG, including total, CM, VLDL, and HDL-TG, and cholesterol, including total, VLDL, and LDL, in dyslipidemic rats with high TG and high cholesterol levels. A recent meta-analysis also revealed that pema brate signi cantly reduced TG levels [31]. Takei et al reported that pema brate (K-877) is a potential PPARα-modulating drug to treat hyperlipidemia that works well in both the liver and small intestine of LDL receptor knockout (Ldlr -/-) mice [32].…”
Section: Discussionmentioning
confidence: 99%
“…This effect, combined with abnormal metabolism of glucose, high incident rates of hypertension and renal dysfunction, and increased BMI, might contribute together to atherosclerosis, cardiovascular diseases and death in diabetic patients. ANGPTL8 is related to HDL-C dysfunction and is involved in the association between dyslipidaemia and arteriosclerosis [27], regardless of glucose intolerance or diabetes mellitus [43,44]. ANGPTL8 presents a negative effect on HDL-mediated cholesterol e ux capacity [17] and a strong link with subclinical atherosclerosis [27], and its levels are signi cantly increased in patients with coronary disease, proportional to disease severity [45].…”
Section: Discussionmentioning
confidence: 99%